Study of Thermal Properties of Mixed (PP/EPR)/ABS with Five Model Compatibilizers - Pierre Marcel Anicet Noah; Louis-Max Ayina Ohandja; Rolant Eba Medjo; Salem Chabira; Fabien Betene Ebanda; Patrick Anyouzoa Ondoua (Journal of Engineering)
The influences of incorporating compatibilizers E-EA-MAH, E-MA-GMA, E-AM, SEBS KRATON G, or PP-g-MAH on the thermal properties of mixed (polypropylene/ethylene propylene rubber)/acrylonitrile butadiene styrene (PP/EPR)/ABS have been investigated. DSC investigations have revealed that the incorporation of 5% of ABS in the copolymer (PP/EPR) does not fundamentally affect the thermal properties of the basic copolymer; additionally, the addition of 1.5% of each of the compatibilizers in the basic mixture does not significantly alter the crystallization temperature values and the melting of the -P- sequences. There is a variation of melting enthalpy values of the -P- sequences of 18.23% using SEBS KRATON G and of 10.38% using E-AM-GMA. When the rate of each of the compatibilizers increases to 5%, overall crystallization enthalpies of -P- sequences are almost kept unchanged, except for the case of using the compatibilizer E-AM-GMA with a variation of 8.42%. There is a minor variation of the melting enthalpy of -P- sequences with higher levels of compatibilizer. The incorporation of 5% ABS copolymer in the PP/EPR does not significantly alter the thermal properties of the basic structure of (PP/EPR)/ABS.